1979
DOI: 10.1021/ac50043a060
|View full text |Cite
|
Sign up to set email alerts
|

Trace determination of phenolic compounds in water by reversed phase liquid chromatography with electrochemical detection using a carbon-polyethylene tubular anode

Abstract: A llquld chromatographic system, capable of selectlvely detecting individual phenolic compounds at 1-ppb levels in water, is described. A polymeric-cation-exchange resin column, acidic acetonitrile-water eluent, and an electrochemical detector containing a unique carbon-black/polyethylene tubular anode are employed. Various types of carbon electrodes have been evaluated, as well as elution order and detector sensitivities for numerous phenolic compounds. Applications of the system to water analyses are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(34 citation statements)
references
References 19 publications
0
32
1
1
Order By: Relevance
“…as low as 0.02 have been reported [ 491, and this approach to composite fabrication is an effective way of reducing the amount of conductor required for conductivity [ 521. As noted earlier, the Kel-F composite electrodes [42-481 are examples of segregated composites and exhibit a lowx., Figure 3 shows a plot of log u versus .f for the Kel-F/silver composite electrode [ 15,24,27,31,331. These values reflect the generally higher k. for dispersed composites compared to segregated composites.…”
Section: Composite Electrode Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…as low as 0.02 have been reported [ 491, and this approach to composite fabrication is an effective way of reducing the amount of conductor required for conductivity [ 521. As noted earlier, the Kel-F composite electrodes [42-481 are examples of segregated composites and exhibit a lowx., Figure 3 shows a plot of log u versus .f for the Kel-F/silver composite electrode [ 15,24,27,31,331. These values reflect the generally higher k. for dispersed composites compared to segregated composites.…”
Section: Composite Electrode Conductivitymentioning
confidence: 99%
“…Armentrout et al employed a polyethylene/carbon black dispersed composite electrode for the LCEC determination of phenolic compounds in surface drainage water, in wastewater treatment plant streams, and in recycle waste brine from the production of chlorinated phenols [31]. This electrode material gave a better SIN ratio than other materials tested, including polyethylene/graphite and Teflodgraphite (both dispersed materials) and various forms of impregnated graphite rod.…”
Section: Appliu Tionsmentioning
confidence: 99%
“…The application of high performance liquid chromatography with electrochemical detection for the determination of phenols in ground and waste waters has been reported by several authors (ref. [30][31][32] and the limits of detection for compounds such as resorcinol, phenol, xylenols and chlorinated phenols quoted to be in the 10-8 -lO mol F1 range. The sensitivity is thus much better than corresponding methods employing ultraviolet detection (phenols generally have low extinction coefficients), and should provide a complimentary method to capillary gas chromatography, which is recognised as the forerunner in this area of analysis (ref.…”
Section: Unauthenticatedmentioning
confidence: 99%
“…The RPLC method can give ultrahigh sensitivity in the parts-per-billion (ppb) range (Hoffsommer et al, 1980;Wegman & Wammes, 1983;Lee et al, 1984aLee et al, , 1984b. Other chromatographic methods (Armentrout et al, 1979) include ion-pair chromatography (Tomlinson et al, 1978) followed by RP separation have been reported with a LOD in the (< 0.1 -30) microgram / liter range (Goulden et al, 1973;Chau & Coburn, 1974;Kuehl & Dougherty, 1980;Mathew & Elzerman, 1981;Ribick et al, 1981;Lindinger et al, 1998).…”
mentioning
confidence: 99%